2008
DOI: 10.1111/j.1551-2916.2008.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure–Property Relationships in Liquid Phase‐Sintered High‐Temperature Bismuth Scandium Oxide‐Lead Titanate Piezoceramics

Abstract: High‐temperature piezoelectrics are necessary for aeronautic and aerospace applications. The principal challenge for the insertion of piezoelectric materials is their limitation for upper use temperature, which is due to low Curie temperature and increasing conductivity at high temperatures. We investigated processing, microstructure, and property relationships of (1−x)BiScO3−(x)PbTiO3 composition as a promising high‐temperature piezoelectric. The effects of excess PbO and Bi2O3 and their partitioning in grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
1
34
1
Order By: Relevance
“…At the saturation state of the polarization (Fig. 4a), the P r and E c of the BS-PT-II ceramic sintered at 1000 C for 2 h are 43.2 mC/cm 2 and 30.9 kV/cm, respectively, higher than the previously reported values [5][6][7][8][9]15,16,26,27,30]. The switching current-electric field curve exhibits two slightly asymmetric peaks with peaks value 10 and À12 A/m 2 , respectively.…”
Section: Methodscontrasting
confidence: 44%
See 2 more Smart Citations
“…At the saturation state of the polarization (Fig. 4a), the P r and E c of the BS-PT-II ceramic sintered at 1000 C for 2 h are 43.2 mC/cm 2 and 30.9 kV/cm, respectively, higher than the previously reported values [5][6][7][8][9]15,16,26,27,30]. The switching current-electric field curve exhibits two slightly asymmetric peaks with peaks value 10 and À12 A/m 2 , respectively.…”
Section: Methodscontrasting
confidence: 44%
“…The strain behavior results indicate a bipolar strain of 0.4% and a unipolar strain of 0.23% (Fig. 4b and c), respectively, both again higher than previously reported values [5][6][7][8]15,26,27,30].…”
Section: Methodssupporting
confidence: 41%
See 1 more Smart Citation
“…Sehirlioglu et al reported previously that excess Bi 2 O 3 would enhance the resistivity and ferroelectric properties in BiScO 3 -PbTiO 3 . 21 It is speculated that the Bi-rich Bi 46 Fe 2 O 72 impurity phase formed under lower sintering temperatures is also critical to good ferroelectric properties in the BF-PZ-PT ternary solid solution system.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the resisitivity of samples sintered in air is higher than that of those sintered in sacrificial powders throughout the whole temperature range studied. The lower resistivity of sample sintered in sacrificial powders may be attributed to the second-phase at grain-boundary which would cause the decrease in resistance [20]. The resistivity of both samples sintered in air is more than 10 9 cm at 400 • C. The temperature dependence of conductivity was fitted according to the Arrhenius equation:…”
Section: Electrical Characterizationmentioning
confidence: 99%